Integrating English Learning in Islamic Boarding Schools: A Contextual Approach to Mandalika's Tourism Landscape - Abrar, Abrar; Widiati, Bidarita (Lingua Cultura, 2025)
While previous research has extensively explored English language teaching in formal educational settings and urban madrasahs, limited attention has been given to pesantren operating in tourism-influenced environments, particularly regarding how these faith-based institutions balance English language instruction with the preservation of Islamic identity and local cultural values. This research gap is significant given the increasing pressure on pesantren to prepare students for engagement with international tourism while maintaining their traditional religious mission. This study examined the integration of English language education within Islamic boarding schools (pesantren) located in Mandalika, a rapidly growing tourism hub in Central Lombok, Indonesia. The research aims to explore pedagogical practices in integrating English learning and tourism context, student engagement and perception, and institutional challenges and opportunities in delivering English instruction contextualized within local tourism and Islamic values. Using a qualitative case study approach, data were collected through semi-structured interviews, classroom observations, and document analysis at two boarding schools: Nurul Ijtihat Al-Ma'arif NU Lengser and Al-Irsyad Al-Islamiyyah. The findings revealed that teachers employ four main strategies: contextual module development, role-play simulations, cross-disciplinary projects, and limited field studies to embed tourism-based content in English instruction. These methods not only enhance language acquisition but also foster students' cultural literacy and confidence. Students demonstrated good engagement and a positive perception of learning English in tourism-related contexts, viewing it as both a practical skill and a means for religious outreach (da’wah). However, the study also identified critical challenges, including the lack of specialized materials, limited professional development, and ideological tensions regarding cultural preservation. Besides that, the study also found several opportunities for contextually appropriate integration have emerged, namely strengthening pesantren's economic role, multilingual cultural da’wah, and institutional collaborations. The study contributes original insights into contextualized English teaching in faith-based institutions and proposes pathways for culturally sensitive curriculum development that bridge education, economy, and spirituality.